The Management of Fiat Money or Gold Standard in the Financial System - Lathif Lanafir Rifqi; Ana Zahrotun Nihayah (Journal of Finance and Islamic Banking, 2020)
In recent years, several prominent figures in Islamic Economics have called for a reform of the financial system from the concept of fiat money to return to the gold standard system (dinar dirham). The main reason for financial system reform is the perspective that fiat money is considered not resistant to inflation. However, the gold standard system is considered to have various weaknesses namely; physical size is relatively heavy, is not proven to be anti-inflation based on historical records, high production costs, inefficient utilization of production resources, only benefits certain groups, and is vulnerable to payment deficits. In theory, the problem of inflation is caused by the imbalance between supply and demand for money itself. If the money supply is greater than the demand, it will cause inflation. Conversely, if the money supply is less than the demand, then the economic activity will not be smooth. Therefore, this article believes that inflation is not due to the physical form of money (paper or gold ), but is caused by effective money supply and demand management. Therefore, government policies are needed including (a) deregulation of the banking system by nationalizing all banks, (b) playing an active role in intervening in the surge in prices of goods and services (c) promoting Ziswaf institutions.